Preparation and characterization of a coacervate extended-release microparticulate delivery system for Lactobacillus rhamnosus - Alli SMA (Dove Medical Press, 2011)
Sk Md Athar Alli Department of Pharmaceutical Technology, Jadavpur University, Kolkata, West Bengal, IndiaBackground: The purpose of this study was to develop a mucoadhesive coacervate microparticulate system to deliver viable Lactobacillus rhamnosus cells into the gut for an extended period of time while maintaining high numbers of viable cells within the formulation throughout its shelf-life and during gastrointestinal transit.Methods: Core coacervate mucoadhesive microparticles of L. rhamnosus were developed using several grades of hypromellose and were subsequently enteric-coated with hypromellose phthalate. Microparticles were evaluated for percent yield, entrapment efficiency, surface morphology, particle size, size distribution, zeta potential, flow properties, in vitro swelling, mucoadhesion properties, in vitro release profile and release kinetics, in vivo probiotic activity, and stability. The values for the kinetic constant and release exponent of model-dependent approaches, the difference factor, similarity factor, and Rescigno indices of model-independent approaches were determined for analyzing in vitro dissolution profiles.Results: Experimental microparticles of formulation batches were of spherical shape with percent yields of 41.24%–58.18%, entrapment efficiency 45.18%–64.16%, mean particle size 33.10–49.62 µm, and zeta potential around -11.5 mV, confirming adequate stability of L. rhamnosus at room temperature. The in vitro L. rhamnosus release profile follows zero-order kinetics and depends on the grade of hypromellose and the L. rhamnosus to hypromellose ratio.Conclusion: Microparticles delivered L. rhamnosus in simulated intestinal conditions for an extended period, following zero-order kinetics, and exhibited appreciable mucoadhesion in simulated intestinal conditions.Keywords: Lactobacillus rhamnosus, mucoadhesive, microparticles, extended-release, intestine